Bacterial Diversity Profiling around the Orca Seamount in the Bransfield Strait, Antarctica, Based on 16S rRNA Gene Amplicon Sequences - Serrano, Wilbert; Olaechea, Raul; Cerpa Cornejo, Luis Moroni; Herrera, Jose; Indacochea Mejía, Aldo Gonzalo (American Society for Microbiology, 2021)
Hydrothermal vent activity is often associated with submarine volcanism. Here, we investigated the presence of microorganisms related to hydrothermal activity in the Orca seamount. Data profiling of the 16S rRNA gene amplicon sequences revealed a diversity pattern dominated mainly by the phyla Proteobacteria, Acidobacteria, Planctomycetes, and Bacteroidetes.